2012
DOI: 10.1111/j.1095-8649.2011.03203.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and expression analysis of fabp2 gene from common carp Cyprinus carpio

Abstract: Two complementary (c)DNA fragments, including the complete open reading frame of fabp2 from the common carp Cyprinus carpio, were cloned by reverse-transcription polymerase chain reaction (RT-PCR). Both were putative intestinal-type fabp genes, named fabp2a and fabp2b. fabp2b was mainly expressed in the intestine and the brain. This gene, however, was nearly not expressed in the liver, heart, pancreas and muscle. fabp2a was only expressed at a very low level in the intestine. Western blot also showed that Fabp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 27 publications
(28 reference statements)
1
5
0
Order By: Relevance
“…The same expression profile was observed in goat (Wang et al 2015). Moreover, Chen et al (2012) found that FABP2 was mainly expressed in the intestine and the brain from the common carp Cyprinus carpio but was hardly expressed in the liver, heart, pancreas and muscle. This might reflect different expression locations in different species.…”
Section: Discussionsupporting
confidence: 63%
“…The same expression profile was observed in goat (Wang et al 2015). Moreover, Chen et al (2012) found that FABP2 was mainly expressed in the intestine and the brain from the common carp Cyprinus carpio but was hardly expressed in the liver, heart, pancreas and muscle. This might reflect different expression locations in different species.…”
Section: Discussionsupporting
confidence: 63%
“…; Chen et al . ; Venold et al . ), and its nutritional control has also been demonstrated (Jordal et al .…”
Section: Discussionmentioning
confidence: 99%
“…). For immunocytochemistry, larvae and tissues from adult fish were fixed in Bouin's solution and embedded in paraffin, and the 6 µm serial sections of the larvae and tissues were stained with human CYP19A antibody (Chen et al , ). Immunohistochemical analysis shows that CYP19A is distributed in the stroma cells of the connective tissue in adult fish ovaries.…”
Section: Primers Used For Carassius Auratus Gene Cloning and The Exprmentioning
confidence: 99%